A Control Strategy for DFIM to Minimize DC Bus Voltage Fluctuations and Torque Oscillations - G. Venu Madhav; Y. P. Obulesu (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The Direct Power Contro; has many advantages like it avoids the usage of integration of PWM voltages which leads to stable operation even at zero rotor frequency, it is position sensor less and hence will not depend on machine parameters like stator or rotor resistance. In case of network unbalance, if the system is operated with constant active and reactive powers, it leads to oscillations in the electromagnetic torque and currents exchange with the grid will become non- sinusoidal, which is not good for the system as it increases the mechanical stress. In this paper, both the rotor connected converter and grid connected converter are fed with DPC strategy along with that a Torque Oscillations Cancellation scheme is applied to RSC and Proportional Integral control based power references generation strategy without calculating the sequence components and with elimination of DC bus voltage oscillations is applied to stator-side converter in order to achieve non-oscillating torque accompanied by quality improved current exchange with the grid. The simulation results of Doubly Fed Induction Generator with and without fault clearly shows that the performance of the proposed scheme is validated.